Nylon resin and process for its production
Patent Information
- Application Number
- CN202510003064.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-01-02
AI Technical Summary
但尼龙12等长链尼龙的酰胺键密度低于尼龙6、尼龙66,使得其在染色时的上染率、着色效果等较低,不能满足衣物面料对颜色鲜艳度的要求
[0040](1)本发明中提供的特定性能的尼龙树脂,通过优化缩聚工艺,将后缩聚工艺分为二个阶段,分别在正(蒸汽)压以及高真空度下进行反应,优化尼龙树脂的分子链结构,降低树脂在初始加工成型时的结晶度,并将冷结晶热处理所需的温度控制在一定范围,由此得到的尼龙树脂用于织物纤维时,染色性能优异。
Smart Images

Figure BDA0005226000990000061 
Figure BDA0005226000990000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of nylon, and more specifically to nylon resins with excellent dyeing properties and their preparation processes. Background Technology
[0002] The dyeing performance of fibers depends on the dispersibility of the dye and the affinity between the fiber and the dye. Generally, acid dyes contain sodium sulfonate groups, which can bind to the amino groups (-NH) of nylon fibers through ionic bonds or electrostatic interactions, thus providing better dyeing results. From the perspective of dyeing uniformity, acid dyes are the preferred choice for dyeing nylon fibers; therefore, acid dyes are the most widely used and popular application in related industries.
[0003] Compared to conventional nylons such as nylon 6 and nylon 66, long-chain nylons such as nylon 12 have advantages such as low density, good low-temperature toughness, low water absorption, and excellent abrasion resistance. When long-chain nylons such as nylon 12 are made into fibers for textile fabrics, the fabrics have advantages such as lightweight, high strength and abrasion resistance, and high cold resistance. However, the amide bond density of long-chain nylons such as nylon 12 is lower than that of nylon 6 and nylon 66, which results in lower dye uptake and coloring effect during dyeing, and cannot meet the requirements for color vibrancy in clothing fabrics.
[0004] EP2292680B1 uses chemicals containing amino, hydroxyl, or epoxy groups as compatibilizers. The compatibilizers are added to polyamides through screw modification, followed by dyeing with acid dyes, thereby improving the dyeing effect of polyamide fibers. However, screw modification can easily cause the polymer to decompose and turn yellow during processing, and can also introduce impurities. This makes the modified resin prone to breakage problems when spinning, especially when spinning microfibers. In addition, the processing cost will also increase. Summary of the Invention
[0005] To address the aforementioned problems in the prior art, this invention provides a nylon resin and its preparation process. The nylon fibers obtained are dyed at a lower temperature and then subjected to cold crystallization and color fixing at a higher temperature, thereby obtaining nylon fibers with excellent dyeing properties.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] In a first aspect of the present invention, a nylon resin is provided, the nylon resin having the following characteristics:
[0008] (a) The DSC curve of long-chain nylon resin was tested using a rapid scanning calorimeter. The temperature was first increased to 220°C at a rate of 10 K / min, then decreased to 20°C at a rate of 30 K / min, and then increased to 220°C at a rate of 10 K / min. A cold crystallization exothermic peak was generated during the second heating process. The temperature of the exothermic peak was measured to be 75-95°C (preferably 90-95°C), and the exothermic heat of crystallization was 55-75 J / g (preferably 70-75 J / g).
[0009] Cold crystallization should be understood as crystallization that occurs after heating to above the softening temperature or glass transition temperature. The cold crystallization temperature is the temperature at which the first maximum exothermic free energy occurs. Exothermicity means the release of energy.
[0010] (b) The relative viscosity measured at 25 °C and 0.5 g / dL concentration in m-cresol solvent was 2.0-2.2.
[0011] According to the nylon resin provided by the present invention, in some embodiments, the nylon resin further has the following characteristics:
[0012] (c) The molecular weight distribution of nylon resin was determined to be 2.85-3.15 using gel permeation chromatography in hexafluoroisopropanol as a solvent.
[0013] In a second aspect of the invention, a process for preparing the nylon resin is provided, wherein the nylon resin is obtained by copolymerization of diamine and dicarboxylic acid monomers.
[0014] The diamine is preferably an aliphatic diamine, such as an aliphatic linear diamine or an alicyclic diamine, more preferably one or more of 4,4-diaminodicyclohexylmethane (PACM), 3,3-dimethyl-4,4-diaminodicyclohexylmethane (MACM), 4,4-isopropyldicyclohexylamine (PACP), 2,4-methylcyclohexanediamine (HTDA), 1,4-cyclohexanediamine, 1,3-cyclohexanedimethylamine, isophoronediamine, and 1,2-cyclohexanediamine.
[0015] The dicarboxylic acid is preferably one or more of isophthalic acid, terephthalic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, and tetradecanoic acid.
[0016] In some embodiments, the nylon resin preparation process further includes lactam and / or water and / or end-capping agent and / or catalyst.
[0017] The lactam is selected from dodecyl lactam and / or caprolactam.
[0018] The capping agent is selected from one or more of oxalic acid, adipic acid, sebacic acid, terephthalic acid, and isophthalic acid.
[0019] The catalyst is selected from one or more of dibutyl phosphate, sodium hypophosphite, hypophosphite, trimethyl phosphate, or triphenyl phosphite.
[0020] In some embodiments, the preparation process of the nylon resin includes the following steps:
[0021] Diamine, dicarboxylic acid, lactam, water, optional catalyst, and end-capping agent are mixed, and the polymerization reaction is carried out under controlled pressure, temperature, and time to obtain nylon resin.
[0022] Specifically, the reaction pressure is -60KPa to 30KPa, the reaction temperature is 240-300℃, and the reaction time is 5h-15h.
[0023] In a specific embodiment, the preparation process of the nylon resin includes the following steps:
[0024] (1) Mix lactam, diamine, dicarboxylic acid, water and capping agent and react them. Then depressurize the reaction system to atmospheric pressure.
[0025] (2) The reaction system was kept under a pressure of 10-30 kPaG for 1-3 hours;
[0026] (3) The reaction system is evacuated and held at a pressure of -70 to -90 kPaG for 0.5 to 1.5 hours;
[0027] (4) Adjust the reaction system to normal pressure, discharge, cool with water, and granulate to obtain nylon resin.
[0028] In this invention, the total mass fraction of the diamine and dicarboxylic acid relative to the total mass of the nylon resin is 15-25%, and the molar ratio of the diamine to the dicarboxylic acid is (0.8-1.2):(0.8-1.2).
[0029] In this invention, the mass fraction of the capping agent is 0.1-0.5%, preferably 0.2-0.3%, relative to the total mass of the nylon resin.
[0030] In this invention, water is used as an initiator for the ring-opening reaction of lactam and as a solvent for the copolymerized nylon salt. The mass ratio of water to nylon resin is 1:(5-30), preferably 1:(15-20).
[0031] In this invention, the mass fraction of lactam is 74.8-84.8% relative to the total mass of nylon resin;
[0032] In this invention, the reaction temperature in step (1) is 240-280℃ and the reaction residence time is 3-5h.
[0033] In this invention, the reaction temperature in steps (2)-(4) is 240-260℃.
[0034] The total mass of the aforementioned nylon resin in this invention is the sum of the masses of lactam, diamine, dicarboxylic acid, and capping agent.
[0035] This invention optimizes the molecular chain structure of long-chain nylon by using staged polycondensation and controlling reaction pressure and time, thereby reducing the crystallinity of the resin during initial processing and molding. This ensures that the cold crystallization temperature and heat release during the second heating process of the nylon resin meet the specified range. The resulting nylon resin exhibits excellent dyeing performance when dyed.
[0036] In a third aspect of the invention, the nylon resin is provided for use in dyeing fabric fibers.
[0037] In some implementations, after the obtained nylon resin is made into 70D / 24F bundles, the bundles are immersed in an acidic dye solution for dyeing, and then the temperature is maintained in stages. After maintaining the temperature at 60-75°C for 0.5-1h, the temperature is increased to 80-90°C at a rate of 3-5°C / min and maintained for 30-45min.
[0038] The nylon resin provided by this invention is used for textile fibers, with a dyeing rate of 85-99%, preferably 97-99%, and a rubbing fastness of grade 3 or above, preferably grade 4 or above.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The nylon resin with specific properties provided in this invention optimizes the polycondensation process by dividing the post-polycondensation process into two stages, which are carried out under positive (vapor) pressure and high vacuum, respectively. This optimizes the molecular chain structure of the nylon resin, reduces the crystallinity of the resin during initial processing and molding, and controls the temperature required for cold crystallization heat treatment within a certain range. The resulting nylon resin has excellent dyeing performance when used in fabric fibers.
[0041] (1) The molecular chain regularity of the nylon resin described in this invention is poor, which makes it incompletely crystallized in the initial spinning process, thereby reducing the crystallinity of the obtained nylon fiber. This makes it easier for the dye to diffuse from the surface of the nylon fiber to the inside of the fiber when the nylon fiber is dyed at a lower temperature, thereby improving the dyeing rate and dyeing rate of the fiber. After the dyed fiber is raised to a higher temperature and kept at that temperature for a period of time, the nylon fiber recrystallizes and the crystallinity increases, thereby improving the color fixation effect of the fiber and improving the color fastness of the fiber. Detailed Implementation
[0042] To better understand the technical solution of the present invention, the following embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.
[0043] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.
[0044] Dodecyl lactam, 4,4-diaminodicyclohexylmethane, 3,3-dimethyl-4,4-diaminodicyclohexylmethane, 1,4-cyclohexanediamine, dodecanoic acid and isophthalic acid, adipic acid and Acid Red dye 88 are all commercially available raw materials.
[0045] The relative viscosity was measured using a Hangzhou Zhuoxiang IV2000 Ubbelohde viscometer in a 0.5 g / dL m-cresol solution at 25 °C, according to ISO 1628-1:1998.
[0046] Molecular weight distribution (D): The test was performed using Shimadzu LC-20A high performance liquid chromatography with hexafluoroisopropanol as solvent. The number average molecular weight Mn and weight average molecular weight Mw were measured, and D = Mw / Mn.
[0047] DSC curve: The test was conducted using a Mettler DSC 3 (differential scanning calorimeter). The nylon resin was first heated to 220°C at a rate of 10 K / min, then rapidly cooled to 20°C at a rate of 30 K / min, and then heated to 220°C at a rate of 10 K / min. The temperature of the cold crystallization exothermic peak and the amount of heat released during the second heating process were measured.
[0048] The dyeing rate was determined and calculated using the residual liquid method on a 723 spectrophotometer.
[0049] Color fastness to rubbing was tested in accordance with GB / T 3920-1997.
[0050] Comparative Example 1
[0051] In a 1m 3 In a mixing container, add 239.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 28.638 kg of 4,4-diaminodicyclohexylmethane, and 31.362 kg of dodecanoic acid. After heating to 260°C and holding for 3 hours, depressurize the system to atmospheric pressure, maintain a vacuum of -50 kPaG at 250°C for 3 hours, and then discharge the system at 250°C. Water-cool and pelletize to obtain nylon resin.
[0052] Comparative Example 2
[0053] In a 1m 3In a stirred container, 239.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 28.638 kg of 4,4-diaminodicyclohexylmethane, and 31.362 kg of dodecanoic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure, and then evacuated to -10 kPa at 250 °C. The reaction system was held for 2 hours. The vacuum was then further reduced to -25 kPaG, and the reaction system was held for 2 hours. Finally, the vacuum was reduced to -50 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0054] Example 1
[0055] In a 1m 3 In a stirred container, 254.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 21.479 kg of 4,4-diaminodicyclohexylmethane, and 23.521 kg of dodecanoic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 20 kPaG for 1 hour. The system was then evacuated to -80 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0056] Example 2
[0057] In a 1m 3 In a stirred container, 239.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 28.638 kg of 4,4-diaminodicyclohexylmethane, and 31.362 kg of dodecanoic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 20 kPaG for 2 hours. The system was then evacuated to -80 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0058] Example 3
[0059] In a 1m 3 In a stirred container, 224.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 35.798 kg of 4,4-diaminodicyclohexylmethane, and 39.202 kg of dodecanoic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 10 kPaG for 3 hours. The system was then evacuated to -70 kPaG and held for 1.5 hours. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0060] Example 4
[0061] In a 1m 3In a stirred container, 239.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 30.519 kg of 3,3-dimethyl-4,4-diaminodicyclohexylmethane, and 29.481 kg of dodecanoic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 20 kPaG for 1.5 hours. The system was then evacuated to -80 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0062] Example 5
[0063] In a 1m 3 In a stirred container, 224.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 38.149 kg of 3,3-dimethyl-4,4-diaminodicyclohexylmethane, and 36.851 kg of dodecanoic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 30 kPaG for 2 hours. The system was then evacuated to -80 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0064] Example 6
[0065] In a 1m 3 In a stirred container, 254.4 kg of dodecyl lactam, 20 kg of water, 600 g of adipic acid (end-capping agent), 25.14 kg of 4,4-diaminodicyclohexylmethane, and 19.86 kg of isophthalic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 10 kPaG for 2 hours. The system was then evacuated to -80 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0066] Example 7
[0067] In a 1m 3 In a stirred container, 254.4 kg of dodecyl lactam, 20 kg of water, 600 g of adipic acid (end-capping agent), 26.52 kg of 3,3-dimethyl-4,4-diaminodicyclohexylmethane, and 18.48 kg of isophthalic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 20 kPaG for 2 hours. The system was then evacuated to -90 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0068] Example 8
[0069] In a 1m 3In a stirring container, add 224.4 kg of dodecanoic acid, 20 kg of water, 600 g of adipic acid (end-capping agent), 28.877 kg of 1,4-cyclohexanediamine, and 46.123 kg of dodecanoic acid. Heat to 260 °C and hold for 3 hours. Then, depressurize the system to atmospheric pressure and hold the reaction system at 250 °C and 30 kPaG for 3 hours. Vacuum the system to -80 kPaG and hold for 1 hour. After the system returns to atmospheric pressure, discharge it at 250 °C, water cool it, and pelletize it to obtain nylon resin.
[0070] Example 9
[0071] In a 1m 3 In a stirring vessel, 254.4 kg of dodecyl lactam, 20 kg of water, 600 g of adipic acid (end-capping agent), 34.849 kg of 1,4-cyclohexanediamine, and 40.151 kg of isophthalic acid were added. The mixture was heated to 260 °C and held for 3 hours. Subsequently, the system was depressurized to atmospheric pressure and reacted at 250 °C and 30 kPaG for 2 hours. The system was then evacuated to -90 kPaG and held for 1 hour. After the system was restored to atmospheric pressure, it was discharged at 250 °C, water-cooled, and pelletized to obtain nylon resin.
[0072] Test case
[0073] The nylon resins obtained in Comparative Examples 1-2 and Examples 1-9 were tested for their relative viscosity, molecular weight distribution, temperature and heat of cold crystallization exothermic peak, as well as their coloring rate and color fastness after dyeing.
[0074] Table 1. Test results of nylon resin in Comparative Examples 1-2 and Examples 1-9
[0075]
[0076]
[0077] Those skilled in the art will understand that modifications or adjustments can be made to the present invention based on the teachings of this specification. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A nylon resin, characterized in that, The DSC curve of the nylon resin was tested using a rapid scanning calorimeter. The temperature was first increased to 220°C at a rate of 10 K / min, then decreased to 20°C at a rate of 30 K / min, and then increased to 220°C again at a rate of 10 K / min. During the second heating process, a cold crystallization exothermic peak was generated. The temperature of the cold crystallization exothermic peak was 75-95°C, and the heat released by cold crystallization was 55-75 J / g. The method for preparing the nylon resin includes the following steps: (1) mixing lactam, diamine, dicarboxylic acid, water and end-capping agent and then reacting them, and then depressurizing the reaction system to atmospheric pressure; (2) The reaction temperature is controlled at 240-260℃, and the reaction system is kept at 10-30KPaG for 1-3h; (3) The reaction temperature is controlled at 240-260℃, and the reaction system is evacuated and held at a pressure of -70 to -90 kPaG for 0.5-1.5 h; (4) The reaction system is restored to normal pressure, and the discharged material is cooled and pelletized to obtain nylon resin.
2. The nylon resin according to claim 1, characterized in that, The DSC curve of the nylon resin was tested using a rapid scanning calorimeter. The temperature was first increased to 220°C at a rate of 10 K / min, then decreased to 20°C at a rate of 30 K / min, and then increased to 220°C at a rate of 10 K / min. During the second heating process, a cold crystallization exothermic peak was generated. The temperature of this cold crystallization exothermic peak was 90-95°C, and the heat released during cold crystallization was 70-75 J / g.
3. The nylon resin according to claim 1 or 2, characterized in that, The relative viscosity measured in m-cresol solvent at 25°C and a concentration of 0.5 g / dL is 2.0–2.
2.
4. The nylon resin according to claim 3, characterized in that, The molecular weight distribution of nylon resin in hexafluoroisopropanol solvent was determined to be 2.85-3.15 using gel permeation chromatography.
5. The nylon resin according to claim 1, characterized in that, In the nylon resin preparation method, the reaction temperature in step (1) is 240-280℃ and the reaction residence time is 3-5h.
6. The nylon resin according to claim 1, characterized in that, In the method for preparing nylon resin, the diamine is an alicyclic diamine.
7. The nylon resin according to claim 6, characterized in that, In the method for preparing nylon resin, the diamine is one or more selected from 4,4-diaminodicyclohexylmethane, 3,3-dimethyl-4,4-diaminodicyclohexylmethane, 4,4-isopropyldicyclohexylamine, 2,4-methylcyclohexanediamine, 1,4-cyclohexanediamine, 1,3-cyclohexanedimethylamine, isophoronediamine, and 1,2-cyclohexanediamine.
8. The nylon resin according to claim 7, characterized in that, In the method for preparing nylon resin, the dicarboxylic acid is selected from one or more of isophthalic acid, terephthalic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, and tetradecanoic acid.
9. The nylon resin according to claim 8, characterized in that, In the preparation method of nylon resin, the lactam is selected from dodecyl lactam and / or caprolactam; And / or: The capping agent is selected from one or more of oxalic acid, adipic acid, sebacic acid, terephthalic acid, and isophthalic acid; And / or: The catalyst is selected from one or more of dibutyl phosphate, sodium hypophosphite, hypophosphite, trimethyl phosphate, or triphenyl phosphite.
10. The nylon resin according to claim 9, characterized in that, In the nylon resin preparation method, the total mass fraction of the diamine and dicarboxylic acid is 15-25% relative to the total mass of the nylon resin.
11. The nylon resin according to claim 10, characterized in that, In the preparation method of nylon resin, the mass fraction of lactam relative to the total mass of nylon resin is 74.8-84.8%.
12. The nylon resin according to claim 1, characterized in that, In the nylon resin preparation method, the mass ratio of water to nylon resin is 1:(5-30).
13. The nylon resin according to claim 12, characterized in that, In the nylon resin preparation method, the mass ratio of water to nylon resin is 1:(15-20).
14. The use of the nylon resin according to any one of claims 1-13 in the preparation of woven fibers.
Citation Information
Patent Citations
Transparent long-chain polyamide and preparation method thereof
CN117801264A